The Effect of Fixator Type on the Color Fastness of Cotton Fabric Dyeing with Mango Leaves Extract (Mangifera indica L.) - Shofi Fahia Anbarwati; Adhi Kusumastuti; Retno Marlangen (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
The effect of different fixatives—alum (Al₂(SO₄)₃·18H₂O), ferrous sulfate (FeSO₄·7H₂O), and lime (Ca(OH)₂)—on the color fastness of cotton fabric dyed with natural dye extracted from mango leaves (Mangifera indica L.) was investigated. The dyeing process involved boiling fresh mango leaves, applying multiple dyeing cycles, and subsequent fixation treatments. Color fastness to washing (ISO 105-C06) and wet rubbing (ISO 105-X12) was evaluated using the gray scale, and data were analyzed with the Kruskal–Wallis test followed by Dunn’s post-hoc test. Results showed that fixative type significantly affected wash fastness (p = 0.018), with lime providing the highest mean rank, followed by alum and ferrous sulfate. In contrast, fixative type had no significant effect on wet rubbing fastness (p = 0.264). These findings indicate that alkaline fixation with lime enhances wash durability of mango leaf dyes, while wet rubbing resistance is less influenced by fixative selection. This study supports the potential of mango leaf extract as an eco-friendly dye source and provides insights for optimizing mordant selection in sustainable textile dyeing applications.